2020
DOI: 10.1136/heartjnl-2020-316624
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence rates of atrial fibrillation in Norway 2004–2014

Abstract: ObjectiveTo study time trends in incidence of atrial fibrillation (AF) in the entire Norwegian population from 2004 to 2014, by age and sex, and to estimate the prevalence of AF at the end of the study period.MethodsA national cohort of patients with AF (≥18 years) was identified from inpatient admissions with AF and deaths with AF as underlying cause (1994–2014), and AF outpatient visits (2008–2014) in the Cardiovascular Disease in Norway (CVDNOR) project. AF admissions or out-of-hospital death from AF, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…Furthermore, in all Nordic countries, citizens have an individual identification number, which makes it possible to combine national register data. Nationwide register studies of AF have been published from Nordic countries merging also data from several separate registers [13][14][15]. However, these countries do not have a national primary health care registry, and nationwide studies have been based only on cases found in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in all Nordic countries, citizens have an individual identification number, which makes it possible to combine national register data. Nationwide register studies of AF have been published from Nordic countries merging also data from several separate registers [13][14][15]. However, these countries do not have a national primary health care registry, and nationwide studies have been based only on cases found in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of people are affected by atrial fibrillation (AF), and the prevalence is estimated to grow rapidly because of an aging population. 1 , 2 , 3 In addition to considerable limitations in quality of life, the incidence of major cardiac events, such as ischemic stroke, heart failure, and death, is substantially increased in people with AF. 4 , 5 , 6 , 7 Recent efforts mainly focus on the prevention of ischemic stroke and treatment of AF through ablation procedures, and progress has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“… 2 It was estimated that the age-standardized prevalence of AF in adults ranged between 2% and 4%, with an increase of 2.3 times. 3 , AF has now become a considerable healthcare cost burden as well as a critical public health issue in China. 4 …”
Section: Introductionmentioning
confidence: 99%